Characteristics of Six types of Motor Performance Tests in Relation to the Body Size of Young Children - Yamate, Takafumi; Takigawa, Koji; Mimura, Kan-ichi (European Journal of Applied Sciences, 2025)
A physical measurement and motor performance test were conducted on 940 preschool children aged 4 to 6 years. The results showed that the performance records in the six motor ability test items improved with age. Gender differences were observed in the 25-meter run, standing long jump, and tennis ball throw, with boys demonstrating better performance than girls. In the five-point evaluation, the percentage of boys classified as A or B (higher motor skill group) decreased from 4.0 to 5.0 years of age, then increased until 6.0 years of age, but decreased again at 6.5 years of age. The percentage of boys classified as D or E (lower motor skill group) increased from 4.0 to 5.0 years of age, then decreased until 6.0 years of age, but increased again at 6.5 years of age. Among girls, the A and B classification rates for the higher motor performance group increased from 4.0 to 5.5 years of age, but then decreased until 6.5 years of age. The D and E classification rates for the lower physical ability group increased from 4.0 to 4.5 years of age, then decreased until 5.5 years of age, but increased at 6.0 and 6.5 years of age. A partial correlation analysis of the overall motor performance scores in early childhood and the six measured items revealed a high correlation with body size. In particular, height, weight, and the Kaup index showed a high correlation with the three items of 25-meter run, standing long jump, and hard tennis ball throw. This suggests that running, jumping, and throwing are the main indicators of motor ability in early childhood.